Conquering in emerging markets: critical success factors to enhance supply chain performance. Issue 3 (3rd April 2017) - Kumar, Vimal; Verma, Pratima; Sharma, R.R.K.; Khan, Ahmad Faraz
Abstract : Purpose: In the context of emerging economies, the purpose of this paper is to seek the critical success factors (CSFs) of supply chain and identify their relationships to enhance the supply chain performance (SCP) in a sample of Indian manufacturing firms. Design/methodology/approach: On the basis of a comprehensive literature review, the authors conducted this study and proposed a new model of antecedent and outcomes for SCP in emerging markets. The empirical data for this study were drawn from a survey of 227 Indian firms, resulting in a response rate of 52 percent. The method of confirmatory factor analysis was applied to refine the CSFs and SCP scale for empirical analysis. The data were analyzed by employing the structural equation modeling technique. Findings: The results reveal that all the identified CSFs, namely, agility, flexibility, flexible innovation, information and communication technology, collaboration among conglomerate divisions, process structure, and training and leadership programs, are positively associated with SCP. The empirical study of 227 Indian firms lent good support to the hypotheses and validates it by the data analysis. Consequently, these findings highlight the prominence of these factors of supply chain for gaining a sustainable competitive advantage in emerging market scenario. Research limitations/implications: The study emphasizes on CSFs in emerging markets that will help to boost the organization's SCP through agility and flexibility in supply chain. This study is applicable for growing markets in which there is ample amount of resources. Originality/value: As economic growth stagnates in developed economies, emerging markets grow at near double-digit rates. Somehow, this study is pioneer in terms of enhance SCP in emerging market scenario. Moreover, the outcome of the study could provide empirical evidence of the effects of CSFs on SCPs.